Transportation and traffic theory : flow, dynamics and human interaction : proceedings of the 16th International Symposium on Transportation and Traffic Theory, University of Maryland, College Park, Maryland, 19-21 July 2005 - Mahmassani, Hani S. (Elsevier, 2005)
Covers a range of aspects of the modelling of transportation processes as complex systems. Recognising that these systems are a collective expression of individual human decisions, this volume is a useful reading for those interested in researching or understanding traffic and transportation phenomena.